Respuesta :

Answer:

An equation of the line that is perpendicular to y-4=2(x-6) and passes thru the point (-3,-5) will be:

  • [tex]y=-\frac{1}{2}x-\frac{13}{2}[/tex]

Step-by-step explanation:

We know the point-slope form of the line equation is

[tex]y-y_1=m\left(x-x_1\right)[/tex]

where

  • m is the slope of the line
  • (x₁, y₁) is the point

Given the line

y-4 = 2(x-6)

comparing with the point-slope form of the line equation

The slope = m = 2

We know that a line perpendicular to another line contains a slope that is the negative reciprocal of the slope of the other line, such as:

slope = m = 2

so, the slope of the line perpendicular to y-4 = 2(x-6) will be:

– 1/m = -1/2 = -1/2

substituting the values of the slope = -1/2 and the point (-3, -5)

[tex]y-y_1=m\left(x-x_1\right)[/tex]

[tex]y-\left(-5\right)=-\frac{1}{2}\left(x-\left(-3\right)\right)[/tex]

[tex]y+5=-\frac{1}{2}\left(x-\left(-3\right)\right)[/tex]

[tex]y+5=-\frac{1}{2}\left(x+3\right)[/tex]

Subtract 5 from both sides

[tex]y+5=-\frac{1}{2}\left(x+3\right)[/tex]

Simplify

[tex]y=-\frac{1}{2}x-\frac{13}{2}[/tex]

Therefore, an equation of the line that is perpendicular to y-4=2(x-6) and passes thru the point (-3,-5) will be:

  • [tex]y=-\frac{1}{2}x-\frac{13}{2}[/tex]